(untitled) (Revista Electrónica REDINE, 2018)
The new social paradigm of university management, passes through an epistemological and cultural break the bureaucratic paradigm, which involves passing the culture of I control a synergetic management teamwork led by leaders in educational organizations with social commitment to deploy knowledge under the best conditions for innovation, change and creativity. it must be an adaptive management that promotes strategic thinking on all members of the organization, with a flexible organizational structure and user-centric. The complexity representing the University at both the institution mobilized on intellectuality and knowledge management in terms of intense philosophical, ontological and deontological truth-seeking process. Achieved, based on the functional structure of a projection from which you intend to order academic processes that compromise professional training, internal, and the ability to contribute to the orientation of national issues that impact on regional and national development, externals. This double institutional status, highlights the particular social reason wields management (university) from this area, since, as a model or pattern of management supported by personal skills and the opportunities available to achieve the highest corporate goals, it operates in an area whose social production comes amid multiple criteria of effectiveness, many different rationales and explanatory references author which is the University we have.